1994
DOI: 10.1063/1.111265
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-line photoluminescence of excitons localized at GaAs/AlGaAs quantum well inhomogeneities

Abstract: GaAs/AlGaAs single quantum well samples have been investigated by photoluminescence spectroscopy using a probe size of about a micron at low temperature. Thin quantum wells fabricated by molecular beam epitaxy with growth interruptions at the interfaces reveal intense photoluminescence lines with spectral widths below 0.1 meV at the low-energy side of the main luminescence. Mapping the quantum well by scanning the probe shows local emission of these sharp lines, which change in number and in energy with latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(61 citation statements)
references
References 12 publications
3
57
1
Order By: Relevance
“…This weaker contribution would only be effective along the NW growth axis and not along the NW circumference and on its own is not sufficient to achieve the observed full three-dimensional confinement. The such formed 'natural', interface fluctuation QDs have been studied over the past in type-I, direct bandgap GaAs/AlGaAs QWs [37,38,39,40] as well as in type-II, indirect bandgap GaAs/AlAs QWs [41]. The superior optical quality of this type of QDs manifests itself in long exciton coherence times [42] and clean single photon emission [43].…”
Section: Sample and Optical Characterizationmentioning
confidence: 99%
“…This weaker contribution would only be effective along the NW growth axis and not along the NW circumference and on its own is not sufficient to achieve the observed full three-dimensional confinement. The such formed 'natural', interface fluctuation QDs have been studied over the past in type-I, direct bandgap GaAs/AlGaAs QWs [37,38,39,40] as well as in type-II, indirect bandgap GaAs/AlAs QWs [41]. The superior optical quality of this type of QDs manifests itself in long exciton coherence times [42] and clean single photon emission [43].…”
Section: Sample and Optical Characterizationmentioning
confidence: 99%
“…The observation of microroughness on top of the macroscopically flat islands gives support to this model. 10 Additionally, PL with spatial resolution 11,12 and near-field spectroscopy 13 showed that the PL line shape is composed by the superposition of many very narrow lines ͑some eV wide͒ that are associated with excitons localization by different lateral-potential fluctuations. Then, the farfield spectrum, i.e., the traditionally observed PL spectrum, is interpreted as an envelope of the very narrow lines associated with defects of different sizes.…”
mentioning
confidence: 99%
“…11 In this sense the lateral dimension ␦ 2 extracted from the Singh and Bajaj equation has to be interpreted as an effective lateral-interface-microroughness size.…”
mentioning
confidence: 99%
“…(12)) diverges when the energy of the intermediate state coincides with the initial or final state. To remove this divergence, we take into account the finite lifetime of the intermediate level and add a small broadening parameter (an order-of-magnitude estimate is 0.1meV 16,17,18 ) to the energy of the intermediate state to convert this divergence into a resonance near the degeneracy point. 19 This broadening parameter is not crucial for our calculation and would not change the qualitative behavior of the SFR.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%